Integrating Folk Art Elements into Visual Arts Education to Foster Cultural Awareness - Esanova Lobar Kulmurotovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the pedagogical potential of incorporating folk art elements into visual arts education to enhance students’ cultural awareness and artistic creativity. It discusses methods for using traditional crafts, patterns, and motifs in classroom activities to develop aesthetic perception, cultural literacy, and reflective thinking. The study emphasizes the importance of combining practical, analytical, and creative approaches to foster holistic learning in art education.